2018
DOI: 10.1016/j.jped.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Curricular intervention increases adolescents’ knowledge about asthma: a randomized trial

Abstract: The inclusion of the asthma topic in the curriculum improved knowledge about the disease in a subgroup of students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
4
4
0
1
Order By: Relevance
“…So; accurate identification of asthma triggers often is a requirement for adequate asthma management. In our study level of knowledge were improved significantly post intervention with slightly decrease in follow up phase which agrees with the study of by Coelho et al (2017) which, confirmed that majority of the adolescents had previously unsatisfactory knowledge about asthma. The relief and maintenance treatment were the most unknown issues in their sample.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…So; accurate identification of asthma triggers often is a requirement for adequate asthma management. In our study level of knowledge were improved significantly post intervention with slightly decrease in follow up phase which agrees with the study of by Coelho et al (2017) which, confirmed that majority of the adolescents had previously unsatisfactory knowledge about asthma. The relief and maintenance treatment were the most unknown issues in their sample.…”
Section: Discussionsupporting
confidence: 92%
“…Asthma is the widespread health problem and most common chronic disease among children and adolescents, with a worldwide prevalence of 14 % ( Coelho et al, 2017). In Egypt, the prevalence of asthma in children (2-12 years) is nearly 8.2%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey also revealed that COPD was not highlighted among the top five diagnoses for respiratory symptoms. This is despite evidence that COPD is one of the leading chronic respiratory diseases in low and middle-income countries [26]. These findings confirm the results from a similar study in Masindi district Uganda which revealed that health workers had very low awareness of COPD.…”
Section: Discussionsupporting
confidence: 76%
“…Two experiences on introducing structured lessons on CRDs for schoolers, based on specific publications to facilitate the process, have taken place in Brazil and were presented briefly in GARD General Meeting 2015. One of them is carried out in Salvador da Bahia (22) and the other in Uruguaiana, Rio Grande do Sul (23).…”
Section: Achievements In Advocacy and Raising Recognition Of Crdsmentioning
confidence: 99%